IoT Based Automatic Electric Appliances Controlling Device based on Visitor Counter - Hitesh Kumar Sharma,; Khushwant Singh,; Md Ezaz Ahmed,; Patni, Jagdish Chandra; Yudhvir Singh,; Prashant Ahlawat, (International Journal of Psychosocial Rehabilitation, 2020)
The 21st Centaury is considered the Era of automation and Artificial Intelligence. Electricity and power sectors are required automation in various levels including grid level as well as home appliances level. IoT has played a significant role to achieve automation at home/office level. Home Automation, Smart Cities, Agriculture and many more sectors have used IoT to automate ON/OFF functioning of Electrical appliances/ Machinery. We are adding one more level to this automation where we have developed a device to do ON/OFF function automatically based on person count entering/exiting in/from a room. It will impact an organization financially and environmentally. It will help an organization to use their electrical appliance effectively. Unnecessary usage of appliances can be avoided using this controlling device. This device is designed using basic electronic components.